Integrating principles and tools of decision science into value‐driven watershed planning for compensatory mitigation - Sanchez, Georgina M.; Eaton, Mitchell J.; Garcia, Ana M.; Keisman, Jennifer; Ullman, Kirsten; Blackwell, James; Meentemeyer, Ross K. (Ecological applications, 2023)
Several environmental policies strive to restore impaired ecosystems and could benefit from a consistent and transparent process—codeveloped with key stakeholders—to prioritize impaired ecosystems for restoration activities. The Clean Water Act, for example, establishes reallocation mechanisms to transfer ecosystem services from sites of disturbance to compensation sites to offset aquatic resource functions that are unavoidably lost through land development. However, planning for the prioritization of compensatory mitigation areas is often hampered by decision‐making processes that fall into a myopic decision frame because they are not coproduced with stakeholders. In this study, we partnered with domain experts from the North Carolina Division of Mitigation Services to codevelop a real‐world decision framework to prioritize catchments by potential for the development of mitigation projects following principles of a structured decision‐making process and knowledge coproduction. Following an iterative decision analysis cycle, domain experts revised foundational components of the decision framework and progressively added complexity and realism as they gained additional insights or more information became available. Through the course of facilitated in‐person and remote interactions, the codevelopment of a decision framework produced three main “breakthroughs” from the perspective of the stakeholder group: (a) recognition of the problem as a multiobjective decision driven by several values in addition to biogeophysical goals (e.g., functional uplift, restoring or enhancing lost functionality of ecosystems); (b) that the decision comprises a linked and sequential planning‐to‐implementation process; and (c) future risk associated with land‐use and climate change must be considered. We also present an interactive tool for “on‐the‐fly” assessment of alternatives and tradeoff analysis, allowing domain experts to quickly test, react to, and revise prioritization strategies. The decision framework described in this study is not limited to the prioritization of compensatory mitigation activities across North Carolina but rather serves as a framework to prioritize a wide range of restoration, conservation, and resource allocation activities in similar environmental contexts across the nation.